Diversité et importance de la flore ligneuse de la ville de Sokodé (Centre - Togo) - Samsahatou Tourey; Tchaa Boukpessi; Koffi Djagnikpo Kpedenou; Tanzidani Komlan Thiou Tchamie (VertigO)
Research carried out in the city of Sokodé (Center-Togo) in June 2017 made it possible to assess the diversity of woody species and to raise people's perceptions of their importance. The woods of the concessions, the roads, the establishments, the interstices and the public places were inventoried. In a compartment of a given compartment, the scientific names of the species present have been identified. A total of 118 woody species grouped into 98 genera and 38 families have been identified in 209 records. The Shannon diversity index (4.8 bits) is relatively higher at the establishment level, followed by concessions (4.61 bits), interstices (4.03 bits) then roads (3.7 bits). On the other hand, the fairness of Piélou is higher (0.87) at the road level. The families of Fabaceae (25 species and 22 genera), Moraceae (11 species and 3 genera), Rutaceae (7 species and 4 genera), Apocynaceae (6 species and 5 genera), Arecaceae and Malvaceae (6 species and 6 genera each), Annonaceae (5 species and 3 genera), Bignonaceae (5 species and 5 genera) and Euphorbiaceae (5 species and 4 genera) are the most represented. Microphanerophytes (54.7%) and mesophanerophytes (29.91%) are the most abundant biological types. In terms of phytogeography, the Sudano-Zambezian species (20.41%) are the most represented, followed by the Pantropical species (19.39%). A questionnaire survey was carried out with 120 people in the city of Sokodé. The importance of woody trees in urban areas is recognized by local populations. The main recognized advantage is food (63.5%), to which are added others such as shade (59.5%), rest (41.9%), wind control and erosion (39.9%).The fruits (84.7%), leaves (38.7%), roots (16.7%) and bark (16.7%) of many woody species are harvested to meet the needs of the populations; which mean that they face several threats. In this context, only sustainable management would allow better conservation of this resource in the city of Sokodé.